2019
DOI: 10.1038/s41561-019-0381-z
|View full text |Cite|
|
Sign up to set email alerts
|

Regional stratification at the top of Earth's core due to core–mantle boundary heat flux variations

Abstract: This is a repository copy of Regional stratification at the top of Earth's core due to core-mantle boundary heat flux variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 61 publications
(44 reference statements)
2
59
0
Order By: Relevance
“…This may favour an outer sub-adiabatic thermal stratification, but large thermodynamical uncertainties remain (Williams, 2018). Moreover, Mound et al (2019) pointed out that this outermost stratification may be regional (rather than global), being generated by the lateral variations in heat flux at the coremantle boundary . Stratification may be also sustained by the accumulation of light elements (e.g.…”
Section: Towards Planetary Applications and Beyondmentioning
confidence: 99%
“…This may favour an outer sub-adiabatic thermal stratification, but large thermodynamical uncertainties remain (Williams, 2018). Moreover, Mound et al (2019) pointed out that this outermost stratification may be regional (rather than global), being generated by the lateral variations in heat flux at the coremantle boundary . Stratification may be also sustained by the accumulation of light elements (e.g.…”
Section: Towards Planetary Applications and Beyondmentioning
confidence: 99%
“…Although our simulations approach the limit of what is computationally feasible, they remain far from the parameter regime for the Earth's core. In particular, estimates of the relevant parameters suggest that Ra may be far larger and E far smaller in the Earth than in our simulations (Mound et al, 2019). The value of q is uncertain in the Earth as it requires knowledge of both the temperature structure and thermal conductivity of the lowermost mantle and the total superadiabatic CMB heat flow; nevertheless, its value in the Earth may be an order of magnitude larger than in our simulations (Mound et al, 2019).…”
Section: Introductionmentioning
confidence: 52%
“…An alternative view of core stratification has recently been suggested from numerical modelling in which stratification is caused, rather than opposed, by lateral CMB heat flow variations; furthermore, the resultant stratification is found to be confined into regional lenses, rather than a global layer (Mound et al, 2019). In some cases, 1D averaging over strong and laterally extensive regional inversion lenses can produce an apparent global stratification despite there being radial motion throughout the core including its outermost regions.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we note that the appropriate description of a stratified layer may in fact need to be more complex than a single uniform layer that we assume. Numerical simulations of core flow with heterogeneous CMB heat flux by Mound et al (2019) find that localized subadiabatic regions that are stratified are possible amid the remaining actively convecting liquid. If indeed local rather than global stratification is the more appropriate model for the Earth's outermost core then the condition of requiring an exact Malkus state would not apply, and the constraints on the magnetic field would be weakened by the existence of regions of non-zero radial flow.…”
Section: Further Extensionsmentioning
confidence: 98%
“…It has been found that the inclusion of a thin stable layer in numerical models can act to destabilize the dynamo, through generating a thermal wind which creates a different differential rotation pattern in the core (Stanley & Mohammadi 2008). Additionally many distinctive features of the geomagnetic field are not reproduced, as strong stratification leads to the disappearance of reverse flux patches and suppression of all non-axisymmetric magnetic field components (Christensen & Wicht 2008;Mound et al 2019).…”
Section: Stratification Of Earth's Corementioning
confidence: 99%